Preparedness, Agility, and the Philippine Response to the Covid-19 Pandemic The Early Phase in Comparative Southeast Asian Perspective - Aguilar, Filomeno V, Jr (Archīum Ateneo, 2020)
Was the Philippines prepared for the Covid-19 pandemic? Did the government take early and effective action that can be characterized as strategically agile? This article answers these questions by reconstructing the chronology of the Philippine government’s response to the pandemic during the early phase. It focuses on three issues: virus importation (specifically the first Covid-19 case), testing, and contact tracing. The Philippine response is contrasted with those of Thailand and Vietnam, which, unlike the Philippines, have succeeded in lowering per capita mortality rate. Deficient in strategic agility, the Philippines failed to consider early on a scenario of extreme disease outbreak.